2021
DOI: 10.1088/1674-1056/abeeef
|View full text |Cite
|
Sign up to set email alerts
|

Control of firing activities in thermosensitive neuron by activating excitatory autapse*

Abstract: Temperature has distinct influence on the activation of ion channels and the excitability of neurons, and careful change in temperature can induce possible mode transition in the neural activities. The formation and development of autapse connection to neuron can enhance its self-adaption to external stimulus, and thus the firing patterns in neuron can be controlled effectively. The autapse is activated to drive a thermosensitive neuron, which is developed from the FitzHugh-Nagumo neural circuit by incorporati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…[35] Furthermore, time delay can not only lead to complex bifurcation scenarios, [36] but also regulate effectively the firing frequency of neurons. [37] Other similar studies on single neurons with time delay can be found in Refs. [38][39][40].…”
Section: Introductionmentioning
confidence: 73%
“…[35] Furthermore, time delay can not only lead to complex bifurcation scenarios, [36] but also regulate effectively the firing frequency of neurons. [37] Other similar studies on single neurons with time delay can be found in Refs. [38][39][40].…”
Section: Introductionmentioning
confidence: 73%
“…[30,31] The experimental results also reveal that autapse promotes the accuracy of neuronal firing and regulates the activities of the nervous system. [29,[32][33][34][35][36] Nevertheless, the function of autapses and their contribution to the accuracy of neuronal firing are still unclear. Thus, understanding the effect of autaptic activities on accurate neuronal responses is still critical work.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the paradoxical role of the autapse (a special synapse connecting to the neuron itself widely observed in multiple types of neuron) has attracted much attention, [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] in addition to its common role in modulating electrical behaviors of single neurons and neuronal networks have been studied. [44][45][46][47][48][49][50][51][52][53] For example, inhibitory autapse has been observed in inhibitory interneurons.…”
Section: Introductionmentioning
confidence: 99%